(untitled) (American Journal of Pedagogical and Educational Research, 2023)
Designing is now being practiced by software developers. Software design reflects hierarchical decomposition, which consists of dividing a complex project (problem) into several easily solvable subproblems. Design encompasses the issues associated with creating software and shapes the software development activities from designing the architecture of the software. The design consists of a complex of standards, instructions, methods, incorporating the rules of the methodological support of the software.